2017
DOI: 10.1002/yd.20232
|View full text |Cite
|
Sign up to set email alerts
|

A Mindset for Career Curiosity: Emerging Leaders Working in the Digital Space

Abstract: This chapter addresses the rapid growth of American industry and a proposed framework-the mindset for career curiosity-that can be used to prepare students for quickly evolving 21st-century digital work environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Considerable multidisciplinary research has explored the diverse input and development resources associated with career adaptation (Johnston, 2018;Haenggli and Hirschi, 2020). In addition, researchers have identified a wide range of competency resources (primarily meta-skills) as contributing to successful career adaptation (Bower and Konwerski, 2017;Haenggli and Hirschi, 2020). However, there remains a debate on the skills that contribute to career adaptation (Ward et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable multidisciplinary research has explored the diverse input and development resources associated with career adaptation (Johnston, 2018;Haenggli and Hirschi, 2020). In addition, researchers have identified a wide range of competency resources (primarily meta-skills) as contributing to successful career adaptation (Bower and Konwerski, 2017;Haenggli and Hirschi, 2020). However, there remains a debate on the skills that contribute to career adaptation (Ward et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meta-skills resources Meta-skills (also referred to as human-skills, soft-skills, and transferable-skills) Meta-skills typically incorporate skills such as problem-solving, communications, and literacy, and extend beyond a specific occupational or sector context (Lievens and Sackett, 2012) Meta-skills are not contextual and therefore more stable and perceived to transcend employment uncertainty Evidence suggests that the development of meta-skills is an important predictor of employability (Finch et al, 2013) Past research has identified a wide range of meta-skills as contributing to career adaptation (Bower and Konwerski, 2017;Coetzee and Harry, 2014) Job-specific skills resources Job-specific skills incorporate the knowledge, attitudes, values, and behaviors required to complete specific tasks associated with a role (e.g. accounting, welding) and/or a sector (e.g.…”
Section: Competency Resourcesmentioning
confidence: 99%
“…What is new is a better understanding of characteristics and experiences need to be considered and fostered in/for future leaders. Bower and Konwerski (2017) state that future leaders need to be curious, embrace learning, and be willing to implement and promote new ideas. In other words, emerging leaders need to develop career curiosity.…”
mentioning
confidence: 99%
“…Certainly, the potential pool of emerging leaders is well positioned to embrace the Bower and Konwerski's (2017) attributes, given they approach future leadership roles from a digital age perspective. Who better to embrace career curiosity than millennials?…”
mentioning
confidence: 99%